A Dual-Broadband Printed Dipole Antenna for 2G/3G/4G Base Station Applications - XiongZhi Zhu; JinLing Zhang; Tong Cui; ZhanQi Zheng (International Journal of Antennas and Propagation)
A new dual-broadband printed dipole antenna for base station applications is proposed in this communication. This antenna has three different dipoles with the same feed point and an extra parasitic strip. The two arms of the three dipoles are printed on opposite sides of the substrate and symmetrical on the centerline, but the parasitic strip at the end of the dipole is just put on one side. Besides, a U-shaped reflector is designed at the bottom of the antenna to realize good radiation characteristics in the working frequency. The simulated and measured results show good agreement. The two studied bands are both broadened which, respectively, achieve 36.7% (690–1000MHz) and 47.3% (1710–2770MHz) for the lower and higher bands so as to satisfy the 2G/3G/4G wireless communication, and the corresponding gains of 4-5dBi and 5-6dBi are also obtained.